Mary Boykin Chesnut : A Biography - Muhlenfeld, Elisabeth, 1944- (Book collections on Project MUSE., 1992)
Mary Boykin Miller Chesnut (18231886) is known today for her excellent firsthand account of life in the Confederate States of America. A Diary from Dixie (republished in 1981 as Mary Chesnuts Civil War)is far more than a simple diary, however, for Mrs. Chesnuts drawing room was a social center for many of the most prominent political and military figures in the Confederacy. Elisabeth Muhlenfelds expert biography utilizes Mrs. Chesnuts autobiographical writings, her papers, and those of her family, as well as published sources. It traces her life in South Carolina from her childhood, as the daughter of a governor and United States senator, through her schooling and her marriage to James Chesnut, Jr., the son of a wealthy South Carolina planter.